A bio-inspired device for drag reduction on a three-dimensional model vehicle. (10th March 2016) - Kim, Dongri; Lee, Hoon; Yi, Wook; Choi, Haecheon
Abstract: In this paper, we introduce a bio-mimetic device for the reduction of the drag force on a three-dimensional model vehicle, the Ahmed body (Ahmed et al 1984 SAE Technical Paper 840300). The device, called automatic moving deflector (AMD), is designed inspired by the movement of secondary feathers on bird's wing suction surface: i.e., secondary feathers pop up when massive separation occurs on bird's wing suction surface at high angles of attack, which increases the lift force at landing. The AMD is applied to the rear slanted surface of the Ahmed body to control the flow separation there. The angle of the slanted surface considered is 25° at which the drag coefficient on the Ahmed body is highest. The wind tunnel experiment is conducted at Re H = 1.0 × 10 5 –3.8 × 10 5, based on the height of the Ahmed body ( H ) and the free-stream velocity ( U ∞ ). Several AMDs of different sizes and materials are tested by measuring the drag force on the Ahmed body, and showed drag reductions up to 19%. The velocity and surface-pressure measurements show that AMD starts to pop up when the pressure in the thin gap between the slanted surface and AMD is much larger than that on the upper surface of AMD. We also derive an empirical formula that predicts the critical free-stream velocity at which AMD starts to operate. Finally, it is shown that the drag reduction by AMD is mainly attributed to a pressure recovery on the slanted surface by delaying the flow separation and suppressing the strength of the longitudinal vortices emanating from the lateral edges of the slanted surface.